Analisis Relevansi Bentuk, Makna, dan Fungsi Syair Adat dalam Upacara Segang sebagai Penguatan Pangan Lokal oleh Suku Soge di Maumere - Katharina Woli Namang; Gisela Nuwa; Elisabeth Henderika Dua Neang (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This research is driven by the threat of losing the oral tradition of the Soge Tribe in Maumere, NTT, due to modernization, youth migration, and climate change disrupting local food security, with the Segang Ceremony serving as a vital ritual preserving agroecological wisdom. The aim is to analyze the relevance of the form, meaning, and function of Segang traditional chants to strengthen local food security amidst these challenges. The method employs qualitative ethnography through participatory observation and in-depth interviews with 12 informants, including tribal elders, farmers, and community members, conducted from August to September 2025, with data collected and processed thematically. Findings reveal the chants' form as three-part rhymed poetry with an adaptive bamboo flute rhythm, symbolic meaning of harmony between nature and ancestors supporting soil fertility and climate adaptation, and a function in passing down agroecological values through crop rotation and communal work, with a relevant example being the chant "Ina Pare, wair uran, tana subur, leluhur berkah," which carries a fertility prayer meaning and motivates crop rotation for food security. Implications include recommendations for revitalization through annual festivals and digital recordings to enhance youth and women engagement, supporting sustainable food self-sufficiency, and contributing to local policies for cultural preservation and food security, though limitations in sample size and regional scope suggest the need for more comprehensive future research.